Expectations, reality and performance in the Finnish biotechnology business - Tuomo Nikulainen; Antti-Jussi Tahvanainen; Martti Kulvik (The Research Institute of the Finnish Economy (ETLA), 2012)
In this paper our aim is to assess the evolution of the Finnish biotechnology sector during the 2000's. Particular focus is given to the growth expectations and realized outcomes of Finnish biotechnology companies, to the evolution of public investments, and to potential determinants of company performance in the sector. The empirical results suggest that there is considerable disparity between the companies' growth expectations and actual performance. Roughly one third of the expected sales have materialized. That being said, it should be noted that the sector has witnessed a significant increase in terms of sales and employment. At the same time, the scale of public funding has dramatically fluctuated during the 2000's in part due to public policy changes and in part due to the financial crisis towards the end of the decade. We also aim to identify where the growth in the sector has come from by discussing company growth and profitability. The findings provide important implications for policy makers regarding the potential evolution paths of the Finnish biotechnology business.
Keywords: O30; M21; L25; 330; biotechnology; industry evolution; growth expectations; public investments; company performance